منهج تعدد الزوجات في الشريعة الاسلامية - صالح الكوربو د. محمد السايح (Aljameai)
المستخلص: تتناول هذه الدراسة بالعرض والتحليل موضوع منهج تعدد الزوجات في الشريعة الاسلامية، حيث تهدف إلى دراسته وعرضه بطريقة حديثة من خلال عرض الآراء المنقسمة حوله والتي تباينت من الوجوب إلى الإباحة، من خلال الرجوع إلى أقوال المذاهب الفقهية الاربعة ومحاولة التوفيق بينها ما أمكن، وقد ختمت هذه الدراسة باستعراض أهم النتائج التي اسفرت عنها. Abstract: This study deals with the presentation and analysis of the topic of the polygamy approach in Islamic law, as it aims to study it and present it in a modern way by presenting the divided opinions about it, which varied from obligation to permissibility, by referring to the statements of the four schools of jurisprudence and trying to reconcile them as much as possible. This study has concluded the study reviews the most important results it yielded.